2016
DOI: 10.7567/jjap.55.07kf17
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of high-voltage staircase drive circuit waveform for high-intensity therapeutic ultrasound

Abstract: Recently, in the treatment of diseases such as cancer, noninvasive or low-invasive modality, such as high-intensity focused ultrasound (HIFU), has been put into practice as an alternative to open surgery. HIFU induces thermal ablation of the target tissue to be treated. To improve the efficiency of HIFU, we have proposed a “triggered-HIFU” technique, which uses the combination of a short-duration, high-voltage transmission and a long-duration, medium-voltage transmission. In this method, the transmission devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These harmonics can be within the bandwidth of HIFU transducers which are highly resonant devices that produce acoustic energy at their harmonics [44], [45]. These harmonics could cause unwanted effects [46], such as disruption of the focal region [41], heating of the transducer [47], and the generation of grating lobes [48].…”
Section: Switching Schemes and Amplifier Designmentioning
confidence: 99%
See 1 more Smart Citation
“…These harmonics can be within the bandwidth of HIFU transducers which are highly resonant devices that produce acoustic energy at their harmonics [44], [45]. These harmonics could cause unwanted effects [46], such as disruption of the focal region [41], heating of the transducer [47], and the generation of grating lobes [48].…”
Section: Switching Schemes and Amplifier Designmentioning
confidence: 99%
“…Alternatively, additional levels can be introduced to the circuit to implement staircase converters. This naturally disrupts the generation of harmonics [52] and several authors have demonstrated harmonic reduction this way at ever increasing frequencies and powers [47], [53]. However, the constraints placed on the waveform with these techniques mean that each array element would require its own adjustable supply to achieve apodisation which is costly and cumbersome.…”
Section: Switching Schemes and Amplifier Designmentioning
confidence: 99%
“…The function generator utilized a CMOS synthesizer (AD9851, Analog Device, Norwood, MA) to produce pulse-width modulated (PWM) signals with duty cycles ranging from 20 to 80% at 2 MHz frequency. The high-voltage ultrasonic signal transmission, with a PWM voltage amplitude up to 50 V, was achieved using four high-speed dual MOSFET drivers (MD1213, Microchip Technology, Chandler, AZ) and N- and P-channel MOSFETs (TC6320, Microchip Technology, Chandler, AZ) [2325]. A maximum amplitude of 50 V was selected in the present study to achieve the target temperature (around 60 °C) with minimum driver size.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, in a high-intensity focused ultrasound (HIFU) system with multi-channel focusing, to realize a compact and highly reliable ultrasonic transmission circuit is a major challenge. We have already proposed a four-stage high-voltage staircase HIFU transmission circuit 1) , which has a pair of P-channel and N-channel MOSFETs for each power supply stage, and reported its effectiveness. The proposed method could reduce the excessive spike noise caused by the switching operation of the MOSFET, without depending on the load characteristics.…”
Section: Introductionmentioning
confidence: 99%